Gambaran Tingkat Kelelahan Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa di Rumah Sakit - Aprianto Guntur Irawan; Bayu Aji Sismanto (Sabda Abadi Nusantara, 2025)
Background: Chronic kidney disease (CKD) patients undergoing hemodialysis often experience fatigue as one of the most common and disruptive symptoms. Fatigue, if not properly managed, can impact quality of life and adherence to therapy. Objective: This study aimed to determine the level of fatigue in CKD patients undergoing hemodialysis in a hospital. Methods: This study used a quantitative descriptive design with a cross-sectional approach. Forty-seven patients undergoing regular hemodialysis were selected using a purposive sampling technique. Data were collected using a validated questionnaire and analyzed descriptively. Results: The study showed that most patients experienced severe fatigue. Thirty respondents (63.8%) experienced severe fatigue, while 17 respondents (36.2%) experienced mild fatigue. Conclusion: The majority of CKD patients undergoing hemodialysis in a hospital experience severe fatigue. These results highlight the need for greater attention to fatigue management, including a multidisciplinary approach to patient care and education to improve their quality of life.